Evaluasi Kinerja Filter High-Pass Dan Low-Pass Pada Citra Beresolusi Tinggi Menggunakan Matlab - Anita Yulistia; Gita Aulia; Harun Al Rasyid; Mhd Murini Ramadhani; Nabila Intan Zahrani; Supiyandi (Journal Of Informatics And Busisnes, 2024)
This study aims to evaluate the performance of high-pass and low-pass filters on high-resolution images using MATLAB software. High-pass and low-pass filters are two basic techniques in image processing that have different functions. A high-pass filter is used to accentuate details and edges in an image, while a low-pass filter is used to smooth the image and reduce noise. This research covers the application of both types of filters on various high-resolution images, as well as the analysis of filter performance based on image quality metrics such as Peak Signal-to-Noise Ratio (PSNR) and Mean Squared Error (MSE). The results show that the high-pass filter is effective in preserving edge details, but increases the noise level. In contrast, low-pass filters are effective in reducing noise, but may cause the loss of some important details in the image.